2011
DOI: 10.1103/physrevb.83.144410
|View full text |Cite
|
Sign up to set email alerts
|

Iron-vacancy superstructure and possible room-temperature antiferromagnetic order in superconducting CsyFe2xSe

Abstract: Neutron and x-ray powder and single crystal synchrotron diffraction of CsyFe2−xSe2 show the presence of superstructure reflections with propagation vector k=[ 2 5 , 1 5 , 1] with respect to the average crystal structure I4/mmm (a = 4, c = 15Å). The propagation vector star corresponds to the 5 times bigger unit cell given by transformation A=2a+b, B= -a+2b, C= c. A solution for the atomic structure is found in the space groups P 42/n and I4/m with an ordered pattern of iron vacancies corresponding to the iron d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
109
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 12 publications
15
109
0
Order By: Relevance
“…Similar to the analysis of Cs y Fe 2−x Se 2 we have sorted out all irreps (Table 3 of Ref. [8]) and found that the best fit of our data is achieved for the τ 2 and τ 5 /τ 7 irreps for the basis vectors parallel to c-axis (similar as we have found before for Cs y Fe 2−x Se 2 ). The configuration for τ 7 is equivalent to τ 5 after π/2 rotation around c-axis.…”
Section: Samples Experimentalsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to the analysis of Cs y Fe 2−x Se 2 we have sorted out all irreps (Table 3 of Ref. [8]) and found that the best fit of our data is achieved for the τ 2 and τ 5 /τ 7 irreps for the basis vectors parallel to c-axis (similar as we have found before for Cs y Fe 2−x Se 2 ). The configuration for τ 7 is equivalent to τ 5 after π/2 rotation around c-axis.…”
Section: Samples Experimentalsupporting
confidence: 83%
“…For the crystal structure we use the vacancy ordered superstructure model I4/m stated in Ref. [8], for the magnetic structure analysis we use symmetry adapted basis functions of eight irreducible representations (irreps) of I4/m space group and propagation vector k = 0 [8]. The description of the structure model and the magnetic and structure parameters and the details of the refinements are summarized in Table 1.…”
Section: Samples Experimentalmentioning
confidence: 99%
See 2 more Smart Citations
“…When Raman scattering is measured at the (001) plane of the K x Fe 2−y Se 2 sample, two Raman-active phonons (A 1g +B 1g ) of the I4/mmm phase and 18 Raman-active phonons (9A g +9B g ) of the I4/m phase, can be observed. Here, one must have in mind that the x' and y' axes of the I4/m phase are rotated by an angle α (-α for the twin domain), 18 to the corresponding axes (x and y) of the I4/mmm phase, see Fig. 2.…”
mentioning
confidence: 99%